Variations in Recruitment Yield and Characteristics of Participants Recruited Across Diverse Internet Platforms in an HIV Testing Study of Young Adult Men-Who-Have-Sex-With-Men (YMSM) - Roland C. Merchant MD, MPH, ScD; Justin Romanoff MA; Melissa A. Clark PhD; Tao Liu PhD; Joshua G. Rosenberger PhD; Jose Bauermeister MPH, PhD; Kenneth H. Mayer MD (American Journal of Men's Health, 2017)
The Internet is a commonly used medium for recruiting geographically dispersed, smaller populations quickly, such as young adult men-who-have-sex-with-men (YMSM). One approach to improve reach and representativeness is to employ multiple Internet platforms to recruit this hard-to-reach population. The utility of this approach has not been studied adequately, and its impact on the study sample recruited is not yet known. Using data from a study of 18- to 24-year-old HIV-uninfected, Black, Hispanic, and White United States (US) YMSM, this investigation compared advertising and enrollment metrics and participant characteristics of those recruited across Internet platforms. Of the 2,444 participants, their median age was 22 years old; 21% were Black, 37% Hispanic, and 42% White; 90% had been tested for HIV at least once in their life; and 87% reported prior condomless anal intercourse (CAI) with another man. There were noticeable differences across platforms in the number of people accessing the study website, meeting study eligibility requirements, consenting to participate, consenting to participate per day of advertising and per click, as well as costs of advertising per consented participant. Participants recruited also varied across platform by race/ethnicity, geographic area of residence in the US, health-care insurance status, years of formal education, history of HIV testing, and CAI by partner type and sexual positioning. The investigation results indicate that the Internet platforms used for recruitment significantly impact not only enrollment but also diversity and characteristics of the sample obtained and consequently, the observations and conclusions rendered.